Vertical distribution and columnar optical properties of springtime biomass- burning aerosols over Northern Indochina during 2014 7-SEAS Campaign - Sheng Hsiang Wang (2018)
© Taiwan Association for Aerosol Research. In this study, the aerosol optical properties and vertical distributions in major biomass-burning emission area of northern Indochina were investigated using ground-based remote sensing (i.e., four Sun-sky radiometers and one lidar) during the Seven South East Asian Studies/Biomass-burning Aerosols & Stratocumulus Environment: Lifecycles & Interactions Experiment conducted during spring 2014. Despite the high spatial variability of the aerosol optical depth (AOD; which at 500 nm ranged from 0.75 to 1.37 depending on the site), the temporal variation of the daily AOD demonstrated a consistent pattern among the observed sites, suggesting the presence of widespread smoke haze over the region. Smoke particles were characterized as small (Ångström exponent at 440–870 nm of 1.72 and fine mode fraction of 0.96), strongly absorbing (single-scattering albedo at 440 nm of 0.88), mixture of black and brown carbon particles (absorption Ångström exponent at 440–870 nm of 1.5) suspended within the planetary boundary layer (PBL). Smoke plumes driven by the PBL dynamics in the mountainous region reached as high as 5 km above sea level; these plumes subsequently spread out by westerly winds over northern Vietnam, southern China, and the neighboring South China Sea. Moreover, the analysis of diurnal variability of aerosol loading and optical properties as well as vertical profile in relation to PBL development, fire intensity, and aerosol mixing showed that various sites exhibited different variability based on meteorological conditions, fuel type, site elevation, and proximity to biomass-burning sources. These local factors influence the aerosol characteristics in the region and distinguish northern Indochina smoke from other biomass-burning regions in the world.